Pengaruh Strategi Bauran Pemasaran dan Produk Plastik Polyethylene Terhadap Kepuasan Konsumen CV Serba Plastik - Fanny Wijaya; Umar Bakti; Evi Meidasari (Penerbit dan Percetakan CV. Picmotiv, 2024)
This research aims to determine the marketing strategy for polyethylene products that is applied to consumer satisfaction at CV Serba Plastik. This research uses quantitative research, where research using quantitative methods is a process for finding knowledge that uses data in the form of numbers as a tool for analyzing the problem you want to know. The data used in this research are primary data and secondary data, primary data was obtained directly from the sources, through respondents filling out questionnaires and secondary data originating from interviews and documentation. The analysis technique is carried out through validity, reliability, classical assumptions, hypotheses and multiple linear regression. The results of the data obtained were partially rejected by marketing strategies in influencing consumer satisfaction and polyethylene product were accepted as significantly influencing consumer satisfaction. Simultaneously both are able to influence consumer satisfaction. In this way, it influences consumer satisfaction at CV Serba Plastik Plastik Bandar Lampung to maintain sales of polyethylene products which have various brands, types and qualities of good quality.